ANALISIS PERBEDAAN KINERJA KEUANGAN SEBELUM DAN SAAT TERJADINYA COVID-19 PADA PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA - Defel Septian; Ni Putu Diana PD (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
In this research, the background is the presence of the Covid-19 virus. Covid-19 does not only have an impact on the world of health but has an impact on all sectors such as education, people's social life and especially the economy in Indonesia. This study aims to test and analyze whether there is a significant difference in Financial Performance before and at the time of the Covid-19 virus in Indonesia as measured by ratio analysis of liquidity ratios, solvency, profitability, activity. The data used in this study are pharmaceutical companies listed on the Indonesia Stock Exchange, totaling 9 companies with an analytical technique, namely the Pair-Sample T-Test method. Based on the descriptive analysis of the data in this study, it resulted in a decrease in the average performance of financial statements as measured by the liquidity ratio variable with the current ratio indicator, solvency with the dept to asset ratio indicator, profitability with the return on assets indicator, and activity with the total asset turnover indicator. . The results of the paired t-test (Pair-Sample T-Test) in this study, namely the ratio of liquidity and solvency did not have a significant difference, while profitability and activity had a significant difference.